Evolving Methodology to Capture Qualitative Data: A Case of Women Domestic Workers - Kumari, Sumita; Singh, Arun Kr. (National Geographical Journal of India, 2022)
To understand the live reality of domestic women worker's (DWW's), we need to have a proper definition and methodology to specify the problem of domestic women workers belonging to an affected group. In this, we are trying to use appropriate methods to capture the data related to the DWW's. For this here we are using a qualitative approach to obtain in the data. Qualitative methods are an exploratory method of inquiry that typically involves investigating an unknown subject matter, sensitive topics, or difficult to access populations. It is an approach rather than a particular set of techniques. This paper focuses on the rationale qualitative methods used to examine the methodology to capture the live reality of the DWW's of Varanasi city. The qualitative nature of this study reveals insight through it focuses on emerging themes and pattern that developed over the time. Methods used included 400 samples (340 part-time DWW's and 60 employers) which were collected from the four different zones of Varanasi city by purposive sampling technique (mainly used snowball sampling). It also included participant observation; pre/post survey; a collection of data through interviews, FGD's (Focus Group Discussions) and PRA (Participatory Research Action) with DWW's and their employer. In-depth interviews were further transcribed and analysed through NVIVO software. The implication of this study provides one example of a qualitative study of the live reality of the DWW's that outline the various methods used to research in phenomenology and interpretive settings